The extent of using the internet for educational purposes among Faculty members - Bilal Fayiz Obeidat, Mohammad Salman Alkhaza’leh (Opción, 2020)
This study aimed to identify the extent of using the Internet among faculty members at the Hashemite University and their training needs. The descriptive approach was used to suit the nature of the study. As a result, 0.63 of the faculty members used the Internet on a daily basis, (0.25) used it on a weekly basis, and only (0.13) percent used it on a weekly basis. The overall average of internet usage among faculty was (2.25). In conclusion, the researchers recommend to activate the internet as an important source of teaching and to encourage its use on a daily basis.